How Maritime Education System Shapes Students’ Professional Mindset: Mediated by Learning Environment and Self-Directed Learning - Juliandri Hasnur; Syafni Yelvi Siska; M. Kurniawan (Attractive : Innovative Education Journal, 2026)
The problem motivating this study is the limited empirical evidence concerning the mechanisms through which the Maritime Education System shapes students’ professional mindset via the Learning Environment and Self-Directed Learning. This study aims to examine the effect of the Maritime Education System on the formation of students’ professional mindset, with particular attention to the mediating roles of the Learning Environment and Self-Directed Learning. A quantitative approach was employed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with bootstrap procedures to assess path significance. Results show that the Maritime Education System has a direct, positive, and statistically significant effect on students’ professional mindset (O = 0.793; p < 0.001) and significantly influences the Learning Environment (O = 0.762; p < 0.001) and Self-Directed Learning (O = 0.717; p < 0.001); both the Learning Environment (O = 0.507; p < 0.001) and Self-Directed Learning (O = 0.268; p < 0.001) contribute positively to students’ professional mindset. Specific indirect effects X–M1–Y (O = 0.387; p < 0.001) and X–M2–Y (O = 0.192; p < 0.001) were also significant, indicating partial mediation with a larger mediating contribution through the learning environment. Accordingly, future research is recommended to adopt longitudinal designs and test moderators such as internship experience and other contextual variables to strengthen empirical evidence and inform maritime education policy.